The quality of life score and its contributing factors of cancer patients undergoing palliative treatment at Thai Binh Oncology Center - Sang, Truong Van; Nguyen Phuc Kien, Nguyen Thi Loan, Nguyen Thi Van Anh, Dao Van Anh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2022)
Purpose: To describe the quality of life score of cancer patients undergoing palliative treatment at the Oncology Center of Thai Binh General Hospital in 2020-2021 and explore the factors from the supply side service provision that affect the quality of life of these patients. Method: A cross-sectional study was conducted on 198 stage IV cancer patients treated from August 2020 to July 2021. The quality of life score was evaluated using the EORTC QLQ-C30 toolkit version 3 before and after treatment at the Palliative Department. Results: The average scores for comprehensive health, physical, motor, emotional, cognitive, and social functions increased by 17.8, 19.3, 24.1, 18.7, 12.4, and 12.1 points, respectively. Symptoms such as fatigue, nausea and vomiting, pain, and shortness of breath significantly improved after treatment. Conclusion: After treatment, the general health issues and physical functions of patients markedly improved, as reflected in the mean scores. Functional, emotional, and social functions also showed improvement, although financial difficulties increased after treatment.